A Review of Environmental Literacy Learning for Prospective Teachers - Fina Fakhriyah; Siti Masfuah; I Gede Margunayasa (Jurnal Penelitian Pendidikan IPA, 2024)
The urgent need to deal with specific environmental changes globally has made us aware of the importance of environmental literacy skills to achieve new relationships with the environment. This study examines and discusses the development of prospective teachers' environmental literacy. It also seeks to link the findings of the educational environment and the environmental impact of pre-service teacher environmental literacy education to the SLR approach. The literature search was conducted online in the Scopus-indexed database with “environmental literacy” and “pre-service teacher” assisted with Publish or Perish software. Then, the search results found 48 articles, followed by a procedure that included Identification, Screening, Eligibility, and Inclusion for each article. Fourteen articles fit the category, so an in-depth analysis was carried out regarding the application of environmental literacy to the prospective teacher education curriculum. The findings show prospective teachers are primarily concerned with environmental issues; however, this emotional reasoning or treatment perspective does not always translate into engaging behaviors or actions. The complexity of environmental problems makes it difficult for prospective teachers to identify how to be involved in this environmental action. Environmental learning to develop environmental literacy can be applied to the curriculum of prospective teachers. Prospective teachers have enormous potential to influence, providing examples and being role models for students in protecting the surrounding environment.